1987
DOI: 10.1111/j.1471-4159.1987.tb01030.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemistry and Biosynthesis of N‐Acetylaspartylglutamate in Spinal Sensory Ganglia

Abstract: N-Acetylaspartylglutamate (NAAG) is a nervous system-specific dipeptide which has been implicated in chemical neurotransmission. Antisera were prepared against NAAG in order to study its cellular distribution. When these antisera were applied to tissue sections of rat spinal sensory ganglia, NAAG-like immunoreactivity was detected within a subpopulation of relatively large neuronal cell bodies in cervical, lumbar, and thoracic ganglia. In order to confirm the presence of NAAG within these neurons, the dipeptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(77 citation statements)
references
References 45 publications
2
75
0
Order By: Relevance
“…The first reliable report of NAAG biosynthesis in tissue explants demonstrated that incubation of excised rat dorsal root ganglia with cycloheximide or ansinomycin at 200 μM did not inhibit incorporation of radiolabel into the dipeptide (Cangro et al, 1987). In this report, the addition of protein synthesis inhibitors actually increased NAAG biosynthesis, and the authors attributed this to the increased availability of radiolabeled glutamate for NAAG biosynthesis, due to the reduced incorporation of glutamine and glutamate into proteins.…”
Section: Naag Biosynthesis and Protein Synthesis Inhibition-inhibitormentioning
confidence: 70%
See 4 more Smart Citations
“…The first reliable report of NAAG biosynthesis in tissue explants demonstrated that incubation of excised rat dorsal root ganglia with cycloheximide or ansinomycin at 200 μM did not inhibit incorporation of radiolabel into the dipeptide (Cangro et al, 1987). In this report, the addition of protein synthesis inhibitors actually increased NAAG biosynthesis, and the authors attributed this to the increased availability of radiolabeled glutamate for NAAG biosynthesis, due to the reduced incorporation of glutamine and glutamate into proteins.…”
Section: Naag Biosynthesis and Protein Synthesis Inhibition-inhibitormentioning
confidence: 70%
“…It is synthesized enzymatically from NAA and glutamate (Arun et al, 2006;Boltshauser et al, 2004;Cangro et al, 1987;Gehl et al, 2004) and is localized in specific types of neurons throughout the CNS (Anderson et al, 1987;Moffett et al, 1993;Moffett and Namboodiri, 1995;Tieman et al, 1991;Tieman and Tieman, 1996). NAAG is released from synapses in a calcium dependent manner (Williamson et al, 1991), and acts through presynaptic metabotropic glutamate receptors to modulate the release of classical neurotransmitters (Xi et al, 2002;Zhao et al, 2001).…”
Section: Naa and Naag Biosynthesismentioning
confidence: 99%
See 3 more Smart Citations